2018
DOI: 10.1111/ors.12387
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Polo® mint mandibular third molar: a case series

Abstract: Aim: Perforation of mandibular third molars (MTMs) by the inferior dental nerve (IDN) is an uncommon finding. Such cases are thought to carry the highest risk for IDN injury (IDNI) due the entrapment of the nerve within the tooth. This case series aims to highlight the lack of consistency through varying radiographic signs, a perforated MTM may present on 2D imaging. Methods: In this series, 22 cases of perforated MTMs were identified prospectively by cone beam CT. The plain film radiographic images for these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…They found that upward diversion was significantly associated with IAN entrapment; however, the downward diversion was insignificant. Similarly, Pippi [27] and Chopra et al [28] in their respective studies, suggested the upward deviation of the mandibular canal to be highly predictive of IAN injury.…”
Section: Discussionmentioning
confidence: 87%
“…They found that upward diversion was significantly associated with IAN entrapment; however, the downward diversion was insignificant. Similarly, Pippi [27] and Chopra et al [28] in their respective studies, suggested the upward deviation of the mandibular canal to be highly predictive of IAN injury.…”
Section: Discussionmentioning
confidence: 87%
“…Otros estudios revelan que la desviación hacia arriba del CM era bastante predictiva de IANE (Pippi, 2010). Chopra et al sin embargo, concluyó que independientemente de los signos que presente, es imposible detectar estos casos de manera confiable con base en imágenes radiográficas bidimensionales (Chopra, 2019). Si se presentan estos signos, es necesario solicitar una Research, Society and Development, v. 11, n. 8, e55011831276, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i8.31276 9 CBCT.…”
Section: Discussionunclassified